Systematics of the Central African Spiny Reed Frog Afrixalus laevis (Anura: Hyperoliidae), with the description of two new species from the Albertine Rift - Greenbaum, Eli; Portik, Daniel M.; Allen, Kaitlin E.; Vaughan, Eugene R.; Badjedjea, Gabriel; Barej, Michael F.; Behangana, Mathias; Conkey, Nancy; Dumbo, Bonny; Gonwouo, Legrand N.; Hirschfeld, Mareike; Hughes, Daniel F.; et al. (Zootaxa, 2022)
The geographically widespread species Afrixalus laevis (Anura: Hyperoliidae) currently has a disjunct distribution in western Central Africa (Cameroon, Equatorial Guinea, Gabon, and possibly adjacent countries) and the area in and near the Albertine Rift in eastern Democratic Republic of the Congo and neighboring countries. At least two herpetologists have previously suggested that these disjunct populations represent distinct species, and herein, we utilize an integrative taxonomic approach with molecular and morphological data to reconcile the taxonomy of these spiny reed frogs. We sequenced 1554 base pairs of the 16S and RAG1 genes from 34 samples of A. laevis and one sample of A. orophilus (sympatric with eastern populations of A. laevis), and combined these data with previously sequenced GenBank Afrixalus samples via the bioinformatics toolkit SuperCRUNCH. Phylogenetic trees, dated phylogenetic analyses, and species-delimitation analyses were generated with RAxML, BEAST, and BPP, respectively. Eleven mensural characters were taken from multiple specimens of A. laevis and A. orophilus, and compared with paired t-tests and analyses of covariance. These combined results suggested populations of A. laevis in western Central Africa (Cameroon and Bioko Island, Equatorial Guinea) represent one species, whereas populations from the Albertine Rift and nearby forests represent two undescribed taxa that are sister to A. dorsimaculatus. The two new species (A. lacustris sp. nov. and A. phantasma sp. nov.) are distinguished by our phylogenetic and species-delimitation analyses, significant differences in several mensural characters, qualitative morphological differences, and by their non-overlapping elevational distribution.